ACHIEVING THE SDGs TARGETS: WOMEN’S AUTONOMY AND THE CONTINUUM OF MATERNAL AND CHILD HEALTH SERVICES UTILIZATION IN INDONESIA USING IDHS 2017 - Nafiah, Izzun; Samosir, Omas B.; Sastiono, Prani (UI Scholars Hub, 2022)
A reduction of child and maternal mortality is among the targets of the Sustainable Development Goals (SDGs), namely the third goal. An important determinant of child and maternal mortality risk is the utilization of maternal and child health (MCH). This study aims to analyze the relationship between women's autonomy and the continuum of MCH services utilization in Indonesia using IDHS 2017. The unit of analysis was women of childbearing age who were married or living together, gave birth to at least one child in the five years before the survey, and had the last child aged 1 to 3 years, totalling as many as 6,575 samples. The analytical method used is multinomial logistic regression. The dependent variable in this study is the continuity of MCH services utilization and is divided into three categories, namely not a continuum, partial continuum, and whole continuum. The primary independent variable used in this study is women's autonomy with the demographic and socioeconomic factors as control variables. The results show that the proportion of mothers who used all MCH services continuously in Indonesia was 22.14 percent. Utilization of PNC and K4 became the most dominant services from disconnection of every mother from utilizing all MCH services continuously. Mothers with higher autonomy had a higher probability of taking advantage of some and all stages of the continuum of MCH services utilization. Therefore, the government must continue to increase women's autonomy to increase the continuum of MCH services utilization and achieve the SDGs targets.